One-hour Upright Posture is an Ideal Position for Serum Aldosterone Concentration and Plasma Renin Activity Measuring on Primary Aldosteronism Screening - Yin, G.; Zhang, S.; Yan, L.; Wu, M.; Xu, M.; Li, F.; Cheng, H. (Experimental and Clinical Endocrinology & Diabetes, 2012)
The serum aldosterone concentration (SAC) to plasma renin activity (PRA) ratio (ARR) is considered a useful screening test in the differential diagnosis of essential hypertension (EH) and primary aldosteronism (PA). The purpose of this study is to investigate the variation of ARR and compare the screening efficiency of it under different postures.37 patients with PA and 92 patients with EH were recruited in this study. Blood was sampled for measuring SAC and PRA under conditions of overnight recumbency, keeping upright posture for 1 h, 2 h and 4 h. The variation and screening efficiency of ARR under these conditions were compared according to repeated measured ANOVA and ROC curve analysis.In the EH group, ARR measured under recumbency posture was higher than those measured under keeping upright posture for 1 h and 2 h. In the PA group, there is no statistical difference for ARR between any 2 postures. AUCs of ARR measured under 4 conditions were 0.976, 0.995, 0.988, and 0.974 respectively. Cutoff values were ranging from 24.75 ng/dl per ng/ml/h under keeping upright for 2 h to 69.19 ng/dl per ng/ml/h under overnight recumbercy. ARR measured under keeping upright posture for 1 h produced the best characteristic of screening efficiency.Keeping upright posture for 1 h was the ideal position for ARR measuring and using a cutoff value of 35.90 ng/dl per ng/ml/h will have a sensitivity and specificity of 100.00% and 92.30% respectively.
Keywords: aldosterone; aldosterone/plasma renin activity ratio; plasma renin activity; primary aldosteronism